Coastal Women and Sustainable Development: a Literature Review On Policies and Field Realities - Misrina Misrina; Andi Tenri Pada Agustang; Rusman Rasyid (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
This article examines the role of coastal women in sustainable development, focusing on the challenges and opportunities they encounter. Women in coastal areas significantly contribute to fisheries, marine product processing, and environmental conservation. However, they often face various obstacles, including exclusion from decision-making processes and unequal resource access. A gender-based approach is used to explore how empowerment can be achieved through capacity building, enhanced access to technology and capital, and livelihood diversification. Additionally, strengthening social networks and local institutions proves essential for supporting active female participation. Inclusive and gender-sensitive public policies are key to creating an environment that fosters women's empowerment. Through these measures, the empowerment of coastal women is expected to enhance their contributions to sustainable development, strengthen community resilience, and support more sustainable natural resource management.